De quelques problèmes de l’assurance I.A.R.D. au Canada - Parizeau, Robert (Assurances, 1983)
The author is concerned with certain problems in the field of fire, automobile and miscellaneous risks insurance. He describes them and expresses the wish that the state would assist the development of Canadian insurance companies to enable them to meet the foreign challenge which they presently face. Even if foreign competition has a useful function, Canadian companies with their smaller resources should have the measures appropriate to their expansion.